2013
DOI: 10.1021/cs300766d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Enhancements in DNA–Enzyme Nanostructures Mimic the Sabatier Principle

Abstract: Advances in DNA bionanotechnology have led to the ability to create structures with well-defined chemical and physical features at the nanoscale. Such nanostructures can be used to create spatially organized enzymatic cascades that promote substrate channeling and result in enhanced cascade kinetics. Here, we investigate the effects of substrate−scaffold interactions on the catalytic activity of an enzyme−DNA complex using horseradish peroxidase (HRP) and a nanoscale DNA scaffold with three addressable sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 25 publications
7
90
0
Order By: Relevance
“…Experimental evidence suggests that enhancements are likely the result of one or more mechanisms, including 1) increased substrate (reactant) concentrations in close proximity to the enzymes, 2) controlled chemical environments beneficial to enzyme activity, and 3) substrate channeling by proximity and bounded diffusion in cascade reactions. Our previous work demonstrates enhanced catalysis through attraction of enzyme substrates to active sites by means of engineered substrate–DNA binding interactions . Similar effects were observed in enzyme–DNA nanostructures with engineered NAD(H) cofactor swing arms.…”
Section: Introductionsupporting
confidence: 65%
“…Experimental evidence suggests that enhancements are likely the result of one or more mechanisms, including 1) increased substrate (reactant) concentrations in close proximity to the enzymes, 2) controlled chemical environments beneficial to enzyme activity, and 3) substrate channeling by proximity and bounded diffusion in cascade reactions. Our previous work demonstrates enhanced catalysis through attraction of enzyme substrates to active sites by means of engineered substrate–DNA binding interactions . Similar effects were observed in enzyme–DNA nanostructures with engineered NAD(H) cofactor swing arms.…”
Section: Introductionsupporting
confidence: 65%
“…clearly showed that enhancement occurs even if there are individual enzyme pairs on each scaffold and the enhancement effect is permanent. Lin and Wheeldon pointed out that attractive interactions between a DNA scaffold and the substrate can facilitate the transport of the substrate to the enzyme2930, and the model by Idan and Hess18 suggested that the effect could be long-lasting. However, DNA does not attract the negatively charged substrate ABTS31 and the throughput enhancement is caused by facilitated transport and should disappear as the concentration of the intermediate substrate builds up in the reaction vessel.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2, nanobiocatalysts with increased activity are constructed through insertion of nanoparticles into enzyme molecules [23], immobilization of enzymes on the surface of nanoparticle/nanorod/2-dimensional nanomaterials [27,28,34], encapsulation of enzymes in porous supports [37,39], embedding/enveloping enzymes on/in 3-dimensional nanostructured supports [16,48,80]. Horseradish peroxidase was immobilized on a nanoscale DNA scaffold with three addressable sites [72]. The enhanced enzyme activity (>300%) of this nanobiocatalyst was ascribed to preferential binding of the substrates to the minor groove of the double DNA helix.…”
Section: Morphology Effect Of Nanoscale Supportmentioning
confidence: 99%